Mapping Research Trends on Communication Skills in Digital Learning in Higher Education: A Bibliometric Analysis (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The present research aims to map the development and intellectual structure of research on communication skills in digital learning in higher education. The Scopus database was the primary source of data, with 277 publications analyzed using the Biblioshiny interface of the Bibliometrix package in R and VOSviewer to visualize bibliometric networks. Method: The analysis covered publication productivity, the most relevant and influential sources, documents with the highest global citations, keyword frequency, topic trends, and cluster mapping through network and overlay visualization. Results: The results show a significant increase in publications since 2020, with contributions predominantly from the fields of education and health education. Keywords such as online learning, communication skills, and higher education emerged as the main nodes in the research network structure. Cluster visualization indicates a close relationship between interpersonal communication, digital learning technologies, and interactive pedagogical approaches. Temporal analysis reveals a shift in focus from emergency learning responses to strengthening the quality and efficacy of communication within the digital learning ecosystem. Novelty: These findings emphasize the importance of developing more systematic conceptual models and evaluation instruments for communication skills in digital higher education.